1995
DOI: 10.1083/jcb.130.1.169
|View full text |Cite
|
Sign up to set email alerts
|

Lens epithelial cell apoptosis appears to be a common cellular basis for non-congenital cataract development in humans and animals.

Abstract: Abstract. Cataract is a major ocular disease that causes blindness in many developing countries of the world. It is well established that various factors such as oxidative stress, UV, and other toxic agents can induce both in vivo and in vitro cataract formation. However, a common cellular basis for this induction has not been previously recognized. The present study of lens epithelial cell viability suggests such a general mechanism. When lens epithelial cells from a group of 20 cataract patients 12 to 94 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
263
2
10

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 339 publications
(295 citation statements)
references
References 65 publications
(77 reference statements)
10
263
2
10
Order By: Relevance
“…pEGFP-HLE, pEGFP-HaA-HLE and pEGFP-HaB-HLE cells were grown to 100% confluence, then treated with 100 nM staurosporine or 0.01% DMSO (control) for 6 h. Then, the cells were harvested for isolation of genomic DNA and the isolated DNA samples were analyzed with 2.0% agarose gel as described previously. 4 The 123 bp marker from Gibco BRL was shown on the left. STS: staurosporine HaA-and HaB-crystallins prevent staurosporineinduced upregulation of Bak in human lens epithelial cells…”
Section: Haa-and Hab-crystallins Prevent Staurosporineinduced Apoptosmentioning
confidence: 99%
See 2 more Smart Citations
“…pEGFP-HLE, pEGFP-HaA-HLE and pEGFP-HaB-HLE cells were grown to 100% confluence, then treated with 100 nM staurosporine or 0.01% DMSO (control) for 6 h. Then, the cells were harvested for isolation of genomic DNA and the isolated DNA samples were analyzed with 2.0% agarose gel as described previously. 4 The 123 bp marker from Gibco BRL was shown on the left. STS: staurosporine HaA-and HaB-crystallins prevent staurosporineinduced upregulation of Bak in human lens epithelial cells…”
Section: Haa-and Hab-crystallins Prevent Staurosporineinduced Apoptosmentioning
confidence: 99%
“…99 The apoptotic nature of the treated cells was further verified by DNA fragmentation and Hoechst staining as previously described. 4,44,45,99 Protein preparation and Western blotting analysis…”
Section: In Vitro Mutagenesis For Creation Of R116c and R120g Mutantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxidative stress, ultraviolet radiation, and other toxic factors can induce the formation of cataract in vitro and in vivo. 1,11 The formation of senile cataract is a universal ageing process accompanied by numerous morphological and functional changes in the lens cells. This study was undertaken to investigate the molecular characteristic of lens epithelial cells from patients with senile cataract.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, HSPB1 might be involved in cataract, because HSPB1, CRYAA and CRYAB interact with each other and all can negatively regulate apoptotic process (Table 4). Studies suggested that lens epithelial cell apoptosis may be a common cellular basis for initiation of non-congenital cataract formation (Li et al 1995), and inhibition of epithelial cell apoptosis may be one possible mechanism that inhibits cataract development (Nahomi et al 2013). Our results here argue for further experimental studies to test the possible role of HSPB1 CNVs in cardiomyopathy or cataract/blindness in African Americans.…”
Section: Duplication Of Hspb1 and Health Disparities In African Amerimentioning
confidence: 99%